Identification of the Ipomoea nil cDNA clone encoding protein with one transmembrane domain by differential display PCR - Dąbrowska, Grażyna Barbara; Dąbrowski, Henryk Paweł; Richert, Agnieszka (Uniwersytet Mikołaja Kopernika w Toruniu, 2020)
A modified differential display procedure was used to compare Ipomoea nil gene expression under flower inductive and non-inductive light/dark conditions and a 170 bp cDNA fragment was displayed. Screening of the cDNA library from I. nil cotyledons led to the isolation of a 577 bp cDNA clone with high nucleotide and amino acids homology to One Helix Protein (OHP) genes from Arabidopsis thaliana and Deschampsia antartica. The membrane spanning helix of InOHP is 91% identical to the MSH of the A. thaliana OHP. MSH is located in the C-terminal part of InOHP protein and corresponds to third MSH of LHC proteins. InOHP transcripts are numerous in leaves of plants when grown under continuous light and are also present in grown under flower inductive condition but their quantity is lower. Southern analysis showed that InOHP is member of a gene family involved in photoprotection of photosystems against excessive light